스마트 팩토리를 위한 하둡 에코 시스템 및 머신러닝 기반의 고무 공정 데이터 분석 - 사공운(Woon Sagong); 이승철(SeungCheol Lee); 장용훈(Yonghun Jang); 박창현(Changhyeon Park) (정보과학회 컴퓨팅의 실제 논문지, 2020)
3차 산업혁명 이후 급격하게 증가된 데이터로 인해 4차 산업혁명 시대에서는 빅데이터에 대한 처리의 필요성이 부각되고 있다. 또한 국내외 산업 현장은 빅데이터 처리를 통한 스마트 팩토리를 구상 및 진행 중이다. 하지만 국내 산업 현장은 스마트 팩토리를 구축하기 위한 빅데이터 처리 기술력과 인력 부족으로 어려움을 겪고 있다. 본 논문에서는 스마트 팩토리를 구축하기 위해 빅데이터와 하둡 에코 시스템을 기반으로 한 고무 공정 데이터를 분석한다. 고무 생산 공정에서 수집한 빅데이터를 활용하기 위해 하둡 에코 시스템을 이용하여 데이터를 수집하였다. 불량률과 관한 요인 분석을 위해 데이터의 전처리를 수행하였다. 전처리 된 데이터를 통계 분석하여 불량률과 관련한 요인을 확인하였다. 이를 통해 머신러닝 기반의 고무 생산 불량 예측 모델링을 수행하였다. 제안한 모델의 평균 예측 성능은 Macro F1 score 0.8554이며 양품과 불량품은 각 0.8912와 0.8196을 달성하였다. There is an increasing need for big data processing in the era of the 4th industrial revolution, due to the rapid increases in the amounts of data following the 3rd industrial revolution. In addition, domestic and foreign industrial sites are conceiving of and proceeding with the development of smart factories through the use of big data processing. However, domestic industrial sites are experiencing difficulties due to a lack of big data processing technology and the manpower needed to build smart factories. In this paper, we analyze data from a rubber manufacturing process based on big data and Hadoop ecosystem to build a smart factory. Data were collected through the Hadoop eco system to utilize the big data collected during the rubber production manufacturing process. Data preprocessing was performed to analyze the factors related to the defective rate. Statistical analysis of the preprocessed data identified factors related to the defective rate. With this knowledge, we performed machine learning-based rubber production defect prediction modeling. The average predictive performance of the proposed model was a macro F1 score of 0.8554, and good and bad products achieved scores of 0.8912 and 0.8196, respectively. KCI Citation Count: 0